Pemodelan Kinetika Pengeringan Beberapa Komoditas Pertanian Menggunakan Pengering Inframerah - Nok Afifah; Ari Rahayuningtyas; Seri Intan Kuala (agriTECH, 2017)
The drying kinetics study was carried out on agricultural commodities using an infrared dryer at temperature 60 °C. The aim of this study was to determine a drying model and effective moisture diffusivity that showed the drying characteristics of cassava slices, banana slices and groundnut pods. The experiments were conducted at three agricultural commodities (cassava, banana, and groundnut) at two capacity levels of 12 kg and 24 kg. Drying was done by arranging the agricultural material on  tray of 0.5 kg and 1 kg for the treatment of 12 kg capacity and 24 kg capacity, respectively. A total of 24 trays were inserted into the dryer and every hour sample was taken to analyze the water content by gravimetric method. Data was fitted to four drying models and non-linear regression analysis was used to determine model parameters. The models were compared based on their coefficients of determination (R2) between the experimental and predicted moisture ratios. The results showed that the increase of drying capacity would decrease the drying rate for all agricultural commodities. The Page model was showed to the best for describing the drying behaviour for these agricultural products. Effective moisture diffusivity ranged between 1.34x10-10 m2/s - 3.23x10-10 m2/s. ABSTRAKStudi kinetika pengeringan telah dilakukan pada beberapa komoditas pertanian menggunakan pengering inframerah pada temperatur 60 °C. Penelitian ini bertujuan untuk menetapkan  model pengeringan dan effective moisture diffusivity yang menunjukkan karakteristik pengeringan irisan singkong, irisan pisang dan polong kacang tanah. Perlakuan yang digunakan adalah jenis komoditas pertanian (umbi singkong, buah pisang, dan polong kacang) pada dua level kapasitas 12 kg dan 24 kg. Pengeringan dilakukan dengan menata bahan pertanian di atas loyang masing-masing sebanyak 0,5 kg dan 1 kg untuk perlakuan kapasitas 12 kg dan 24 kg. Sebanyak 24 loyang dimasukkan ke dalam pengering dan setiap jam diambil sampel untuk dianalisa kadar airnya dengan metode gravimetri. Data diujikan dengan empat model pengeringan dan analisis regresi non-linear digunakan untuk menentukan parameter model. Nilai rasio kandungan air eksperimental dan hasil prediksi model selanjutnya dibandingkan berdasarkan koefisien determinasi (R2). Hasil penelitian menunjukkan bahwa kenaikan kapasitas pengeringan akan menurunkan laju pengeringan untuk semua komoditas pertanian. Model Page terlihat paling baik untuk menggambarkan perilaku pengeringan bahan-bahan pertanian tersebut. Nilai difusivitas efektif kandungan air berkisar pada 1,34x10-10 m2/detik - 3,23x10-10 m2/detik.